2019
DOI: 10.1177/0267323119844411
|View full text |Cite
|
Sign up to set email alerts
|

Journalism, solidarity and the civil sphere: The case of Charlie Hebdo

Abstract: On 7 January 2015, Said and Chérif Kouachi assaulted the offices of the French satirical weekly Charlie Hebdo, leaving 12 people dead. The terrorist attack soon became a highly symbolic event, reflecting the core struggle between free speech and religious values that escalated after the ‘cartoon crisis’ in 2005. In this article, we wish to explore media discourses in the aftermath of the Charlie Hebdo attack in three European countries – Spain, Norway and the United Kingdom. In particular, we investigate if an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…While analyzing the Editorial of selected newspapers, the researcher has found out The New Zealand Herald and The News International have substantially produced the 'solidarity' discourse. The results show that the media performed a 'solidarity' 'consensus' role in Charlie Hebdo (Luengo & Ihlebaek, 2019). Similarly, the findings of analyzed data in this study show that discourse produced by the selected newspapers is 'positive', 'outgroup', 'civil repair', 'solidarity', and 'harmony'.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…While analyzing the Editorial of selected newspapers, the researcher has found out The New Zealand Herald and The News International have substantially produced the 'solidarity' discourse. The results show that the media performed a 'solidarity' 'consensus' role in Charlie Hebdo (Luengo & Ihlebaek, 2019). Similarly, the findings of analyzed data in this study show that discourse produced by the selected newspapers is 'positive', 'outgroup', 'civil repair', 'solidarity', and 'harmony'.…”
Section: Discussionsupporting
confidence: 70%
“…The Christchurch mosques shootings is not a single incident of its kind rather in quite a recent past there had been a Quebec City mosque shooting in 2017, London Bridge attack in 2017, Copenhagen shootings in 2015 and the Charlie Hebdo attack in 2015 which stunned the whole world. Media all around the world gave specific attention and produced certain kinds of discourses on the incidents ranging from a 'solidarity discourse' Luengo & Ihlebaek, 2019;Ghauri, 2017) to a variety of binary discourses like; 'othering' (Umber, Ghauri & Haq, 2021;, 'Securitization' (Ghauri, Umber & Warrich, 2020;Tsagarousianou, 2016;Mertens & Smaele, 2016;Cesari, 2010), 'political parallelism' Ghauri, 2019a;2019b;Ghauri & Yousaf, 2018;Ghauri, 2018;Tsagarousianou, 2016;Mertens & Smaele, 2016). In such scenarios of conflict, especially within a country, the binary discourses produced by the local press is an act equal to pouring oil on fire.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, research on journalistic performance has shown how the news media often leave their role as critical reporters to take on a ceremonial one in the aftermath of radical events or terrorist attacks (Thorbjørnsrud and Figenschou, 2018). Therefore, journalism can reaffirm core values of the civil sphere in the aftermath of a specific crisis (Alexander, 2006; Luengo and Ihlebæk, 2019).…”
Section: News Media As Emotional Regimesmentioning
confidence: 99%
“…For the European context, the European debt crisis and the migration crisis might be the most dominant issues related to solidarity. Furthermore, we expect that international terrorism and climate change are key issues that have dominated the public discourse in the past decade and that have been associated with solidarity (Kleinen-von Königslöw, Post, & Schäfer, 2019;Luengo & Ihlebaek, 2019).…”
Section: Concludesmentioning
confidence: 99%